Septic loosening of hip endoprosthesis with acetabular protrusion and damage of external iliac artery: case report - Uvarovas, Valentinas; Kocius, Manvilius; Voitkun, Jurij; Kuropatkinaitė, Indrė; Kaupas, Simonas (Lietuvos chirurgija, 2015)
In this article, we describe a rare complication after total hip arthroplasty (THA). Because of the hip arthrosis, a rutine primary arthroplasty was made. During the first month after arthroplasty, four luxations of the endoprosthesis occurred. In one month after primary THA, the revision surgery with a double mobility acetabular component was made because of the loosening of the acetabular component. After 12 months, because of the progressive septic protrusion of the acetabular component, revision surgery was done. An acetabular component protrusion, which damaged the wall of a. illiaca externa, was found. Because of multiple sites of the femus and acetabulus osteomielytis, exarticulation of the hip was done.